2016
DOI: 10.1159/000453610
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of “Lesion-by-Lesion” and Field Photodynamic Therapy in the Prevention of Actinic Keratoses: A Randomized, Split-Face, Single-Blind Pilot Study

Abstract: Background: Actinic keratoses (AKs) are often treated separately, lesion by lesion. However, in the past years, AKs have been described as a field disease and not limited to single clinically apparent lesions. Treatment should therefore target an area of field change which may reduce the risk of development of further AKs, second tumours, and local recurrence. Objective: The primary objective was to determine the number of new lesions at 9 months after methyl aminolevulinate photodynamic therapy (MAL-PDT). Sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Inge Seubring et al treated AK patients with “lesion-by-lesion” methyl aminolevulinate photodynamic therapy (MAL-PDT) and field MAL-PDT. Nine months later, field MAL-PDT significantly reduced AK lesions compared with lesion-by-lesion MAL-PDT32. ALA and its methyl esters (methyl 5-aminolevulinate) are the most effective topical photosensitizers approved for treating actinic keratoses21, 22.…”
Section: Discussionmentioning
confidence: 99%
“…Inge Seubring et al treated AK patients with “lesion-by-lesion” methyl aminolevulinate photodynamic therapy (MAL-PDT) and field MAL-PDT. Nine months later, field MAL-PDT significantly reduced AK lesions compared with lesion-by-lesion MAL-PDT32. ALA and its methyl esters (methyl 5-aminolevulinate) are the most effective topical photosensitizers approved for treating actinic keratoses21, 22.…”
Section: Discussionmentioning
confidence: 99%
“…One AK study comparing lesion-directed MAL-cPDT with field MAL-cPDT demonstrated that, after a single treatment session, both therapies resulted in a significant reduction of lesions at 3 months, 6 months, and 9 months ( p = 0.009). However, at 9 months, the number of new AKs was significantly lower with field therapy compared with lesion-directed therapy ( p = 0.014) [ 30 ]. Another study comparing multiple full-face MAL-dlPDT sessions with cryosurgery [ 31 ] demonstrated no significant difference in AK clearance ( p = 0.154) or number of new AKs ( p = 0.542) between the therapies over 24 months.…”
Section: Prevention Of Field Cancerization and Photorejuvenationmentioning
confidence: 99%